Robbery with Violence as a Criminal Phenomenon in Urban Communities - Hamid, Abdul; Imraan , Mohd (The International Journal of Law Review and State Administration, 2026)
Robbery, as a form of theft accompanied by violence or threats of violence, has become a significant criminal phenomenon in urban societies. Rapid urbanization, population density, socioeconomic inequality, and limited employment opportunities contribute to the increasing occurrence of this crime in metropolitan areas. This study aims to analyze robbery as a criminal phenomenon within urban communities by examining its characteristics, underlying causes, and social impacts. Using a normative-empirical approach, this research combines legal analysis with criminological perspectives to understand how robbery affects public security and social order. The findings indicate that economic pressure, weak social control, and environmental factors play a major role in encouraging individuals to commit robbery. Furthermore, robbery generates fear, disrupts social stability, and reduces public trust in law enforcement institutions. Therefore, comprehensive crime prevention strategies involving law enforcement agencies, local governments, and community participation are essential to effectively address robbery in urban settings. Strengthening preventive measures and improving social welfare are crucial steps toward reducing the incidence of robbery and enhancing public safety.